The Process of Identity Formation of Santung Heroes in Kuala Jambi 1949-1984 - Dani, Novian; Pradita, Dennys; Saumia, Zulfa (Siginjai: Jurnal Sejarah, 2025)
This study examines the formation of the heroic identity of Santung in the Kuala Jambi community using historical research and a collective memory approach. Collective Memory is a collection of memories or past awareness of a group of people that are reinterpreted in the present and become a reflection of life together. Santung is a fighter figure who fought to defend Indonesian independence in Kuala Jambi. Santung was killed when the Dutch attacked Santung's house on January 4, 1949. To appreciate Santung's struggle, the community called Santung a hero from Kuala Jambi, but over time, the story of Santung's heroism gradually faded. This reseach use history method with memry studies approach. The process of remembering carried out by so many people on a certain time scale, and then passed down to the next generation, will form a collective memory structure. Based on these events, the author is interested in revealing the process of forming the heroic identity of Santung in Kuala Jambi